Actions of Expropriation in Family Companies: The Moderating Role of Independent Commissioner’s Control - Pratiwi, Adhitya Putri; Ruhiyat, Endang; Holiawati, Holiawati (JDM (Jurnal Dinamika Manajemen), 2024)
This study examines the effects of the pyramid structure and disclosure of related party transactions on acts of expropriation in family companies with the independent commissioner’s control as a moderation. This research is a type of quantitative research. This research uses secondary data from annual reports from 31 family companies in 2017- 2018. The data analysis techniques in this research are descriptive statistics, panel data regression analysis, and moderated regression analysis. The study finds that the pyramid structure does not affect expropriation, while disclosure of related party transactions has a negative effect on expropriation. The interaction test shows that the mediator variable could not mediate the pyramid structure and expropriation. Conversely, the moderating variable is able to moderate the disclosure of related party transactions and expropriation. The results of this research can provide input to policymakers to tighten regulations regarding protection for minority shareholders. In addition, the results of this research will add to the government’s references in expanding rules related to the disclosure of related party transactions, especially regarding the supervision of related party transactions carried out by companies.